1996
DOI: 10.1128/mcb.16.12.6617
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Dependence of Trinucleotide CAG Repeat Instability in Saccharomyces cerevisiae

Abstract: To examine the chromosomal stability of repetitions of the trinucleotide CAG, we have cloned CAG repeat tracts onto the 3 end of the Saccharomyces cerevisiae ADE2 gene and placed the appended gene into the ARO2 locus of chromosome VII. Examination of chromosomal DNA from sibling colonies arising from clonal expansion of strains harboring repeat tracts showed that repeat tracts often change in length. Most changes in tract length are decreases, but rare increases also occur. Longer tracts are more unstable than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
94
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 24 publications
21
94
1
Order By: Relevance
“…Furthermore, no rearrangements were observed on analyzing individual colonies obtained from transforming the parental plasmids into E. coli HB101. Likewise, rearrangements were not observed previously in other prior instability studies with triplet repeat inserts in E. coli HB101 (10,16,18,19,39,86,(91)(92)(93). This confirms that the rearrangements were because of an intrinsic property of the pcDNA3.1 shuttle vector that carries the SV40 origin of replication.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Furthermore, no rearrangements were observed on analyzing individual colonies obtained from transforming the parental plasmids into E. coli HB101. Likewise, rearrangements were not observed previously in other prior instability studies with triplet repeat inserts in E. coli HB101 (10,16,18,19,39,86,(91)(92)(93). This confirms that the rearrangements were because of an intrinsic property of the pcDNA3.1 shuttle vector that carries the SV40 origin of replication.…”
Section: Resultssupporting
confidence: 64%
“…In case of the tetranucleotide repeats, however, instability refers to both expansions and deletions. Thus, upon initial consideration, our results appear to be similar to the results with the triplet repeat sequences, including CTG⅐CAG, CGG⅐CCG, and GAA⅐TTC, in which orientation II was shown to be more unstable (9,10,16,18,19,21,22,39,52,85,86,95,96). However, the CCTG sequences are genetically unstable in the orientation prone to expand (orientation II) (Fig.…”
Section: Chemical Probe Determinations-d(cagg)supporting
confidence: 72%
See 1 more Smart Citation
“…The disruption of the RAD27 gene of Saccharomyces cerevisiae (a homologue of human flap endonuclease 1, FEN-1) did affect the instability of TNR while the disruption of mismatch or recombination related genes did not change the rates of TNR instability (Maurer et al,1996;Freudenreich et al, 1998). Zakian et al showed that a deletion mutant of RAD27 caused lengthdependent destabilization of CTG tracts and increased in its expansion frequency.…”
Section: Introductionmentioning
confidence: 99%
“…DNA replication (5)(6)(7)(8) and repair including methyl-directed mismatch repair (9 -11), nucleotide excision repair (12), DNA polymerase III exonucleolytic proofreading (13), and double-strand break repair (14) have been implicated.…”
mentioning
confidence: 99%